Differential Expression of KCNJ12 Gene and Association Analysis of Its Missense Mutation with Growth Traits in Chinese Cattle - Jie Cheng (Animals, 2019)
The potassium inwardly rectifying channel, subfamily J, member 12 (KCNJ12) gene is a promising candidate for economic traits because of its crucial roles in myoblast development. Here, a missense mutation (Cys > Arg) was first detected to be located in exon 3 of KCNJ12 from three Chinese cattle breeds by DNA-pool sequencing. Then, we performed an association analysis of this single-nucleotide polymorphism (SNP) with stature in three Chinese cattle populations (n = 820). A significantly positive correlation was revealed by a reduced animal general linear model and the CC genotype was the most favorable in three breeds. Further, we measured the expression profile of the KCNJ12 gene in various cattle tissues and primary bovine skeletal muscle cells. Ubiquitous expression with high abundance in muscle was observed. Further, in primary bovine skeletal muscle cells, the KCNJ12 mRNA expression was gradually up-regulated in differentiation medium (DM) compared with that in growth medium (GM), suggesting that the KCNJ12 gene is involved in bovine myocyte differentiation. Conclusively, the KCNJ12 gene is a functional candidate gene which can be used as a molecular marker for cattle breeding.